(untitled) - Berry, Stephen (Oxford, 2001)
This CD provides a contemporary approach to the study of physical chemistry. By beginning with quantum chemistry, students will learn the fundamental principles upon which all modern physical chemistry is built.
Keywords: Chemistry, physical and theoretical